2021
DOI: 10.1002/hon.127_2880
|View full text |Cite
|
Sign up to set email alerts
|

Sintilimab Plus Chidamide for Relapsed/Refractory (R/R) Extranodal Nk/T Cell Lymphoma (Enktl): A Prospective, Multicenter, Single‐arm, Phase Ib/Ii Trial (Scent)

Abstract: DLT) during cycle 1. Six dose levels were planned. The CRM design allowed more rapid accrual: once the maximum 3 patients were on the dose level under evaluation, further patients received the dose level below, with all data contributing to dose decisions. Ph 2 used a single stage A'Hern design to assess best ORR during the first 8 cycles (assessed using the Revised Response Criteria for Malignant Lymphoma) of the combination in all participants (pts) treated at the MTD. ROMI was given IV on days 1, 8 and 15 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…In this case, the patient experienced only hematologic adverse events, including thrombocytopenia and neutropenia, without immune-related adverse events and severe adverse events. Compared to the previous safety profiles of a phase I/Ib study of PD-1 antibody pembrolizumab plus HDACi vorinostat for non-small cell lung cancer and a phase Ib/II trial of sintilimab plus chidamide for NK/T cell lymphoma, the treatment-related adverse events of this case were consistent with the observations of previous findings, without additional toxicity appearing ( 28 , 30 , 31 ). These findings indicated that the combination of sintilimab and chidamide has a favorable safety profile.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this case, the patient experienced only hematologic adverse events, including thrombocytopenia and neutropenia, without immune-related adverse events and severe adverse events. Compared to the previous safety profiles of a phase I/Ib study of PD-1 antibody pembrolizumab plus HDACi vorinostat for non-small cell lung cancer and a phase Ib/II trial of sintilimab plus chidamide for NK/T cell lymphoma, the treatment-related adverse events of this case were consistent with the observations of previous findings, without additional toxicity appearing ( 28 , 30 , 31 ). These findings indicated that the combination of sintilimab and chidamide has a favorable safety profile.…”
Section: Discussionsupporting
confidence: 89%
“…Two case reports on NK/T cell lymphoma have reported that combined sintilimab and chidamide therapy may lead to successful outcomes ( 28 , 29 ). Moreover, a phase IB/II trial that included 38 patients with R/R extranodal NK/T cell lymphoma who were treated with sintilimab plus chidamide showed an ORR of 59.5% and a CR rate of 48.6% ( 30 ). Although HDACi plus PD-1 antibody treatment is rarely studied in lymphoma, it is often studied in head and neck squamous cell carcinomas, salivary gland cancer, non-small cell lung cancer, and other types of cancer ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results were in line with published data showing greater survival benefit with transplant for patients with high-risk ENKTL (24). An alternative solution is the combination of chemotherapy with novel targeted agents such as PD-1 antibodies, histone deacetylase inhibitors or CD30-antibody conjugates (25)(26)(27). In a phase 2 trial, PD-1 antibody monotherapy produced an ORR of 68% and 1-year OS of 82% in patients with relapsed/refractory ENKTL (25).…”
Section: Discussionsupporting
confidence: 86%
“…In a phase 2 trial, PD-1 antibody monotherapy produced an ORR of 68% and 1-year OS of 82% in patients with relapsed/refractory ENKTL (25). Other clinical trials have reported promising early results of the combination of a PD-1 antibody with a histone deacytelase inhibitor for relapsed/refractory ENKTL (27). Although these agents have not yet been tested in the first-line setting, it is hopeful that results from these trials might eventually change the treatment landscape of ENKTL towards a more riskadapted and individualized approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although anti-PD-1 antibodies or HDACi were associated with modest ORR and duration time when used as a single agent in R/R CTCL, several case reports and clinical studies have shown an enhanced effect of the combination of chidamide plus sintilimab in R/R NK/T cell lymphoma (NKTCL) ( 47 , 48 ). A phase IB/II trial including 38 patients with R/R extranodal NKTCL showed an ORR of 59.5% and a CR rate of 48.6% with a durable response ( 49 ). Moreover, this combination therapy has also achieved efficacy in patients with other types of tumors ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%